Theoretical Challenges for Distance Education in the 21st Century: A Shift from Structural to Transactional Issues - Garrison, Randy (International Review of Research in Open and Distributed Learning, 2000)
The premise of this article is that theoretical frameworks and models are essential to the long-term credibility and viability of a field of practice. In order to assess the theoretical challenges facing the field of distance education, the significant theoretical contributions to distance education in the last century are briefly reviewed. This review of distance education as a field of study reveals an early preoccupation with organizational and structural constraints. However, the review also reveals that the theoretical development of the field is progressing from organizational to transactional issues and assumptions. The question is whether distance education has the theoretical foundation to take it into the 21st century and whether distance education theory development will keep pace with innovations in technology and practice.